Perancangan User Experience Aplikasi Konsultasi Penyakit Hewan Peliharaan menggunakan Pendekatan Human-Centered Design - Satrio Priambudi Saksono; Buce Trias Hanggara; Intan Sartika Eris Maghfiroh (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Pets are susceptible to various diseases and as owners, they are responsible for taking care of their pet's health. However, the comparison of the number of veterinarians and pet owners in Indonesia is not balanced, especially in remote rural areas. This phenomenon can trigger the need for online pet disease consultation services. to ensure that the application design made based on the needs of pet owners has a good level of usability, and can meet the expectations of pet owners, a user experience design is needed in accordance with the application design flow that produces a design with a good level of usability and user experience.The design of the user experience of the pet disease consultation application is carried out with a human-centered design approach. The design process begins with analyzing the context of use for pet consultation applications, then analyzing user needs, namely pet owners, followed by designing pet disease consultation application solutions, and testing the design of pet disease consultation application solutions that have been made using the usability testing method to 5 pet owners with the results of effectiveness testing getting a score of 100% testing, and in efficiency testing getting a score of 100%. After that, user perception measurements were taken using the user experience questionnaire method with